Short- and long-term exposure to air pollution increases the risk of stroke. Issue 6 (July 2022) - Kim, So Young; Kim, Joo-Hee; Kim, Yoo Hwan; Wee, Jee Hye; Min, Chanyang; Han, Sang-Min; Kim, Seungdo; Choi, Hyo Geun
Objective: Many epidemiological studies have observed the association of air pollutant exposure with the onset, progression, and mortality of stroke. The aim of this study was to investigate the associations of air pollutants, including SO2, NO2, O3, CO, and PM10, with stroke according to exposure duration. Methods: Data from the Korean National Health Insurance Service-Health Screening Cohort from 2002 to 2015 were obtained. The 21, 240 patients who were admitted for or died due to stroke were 1:4 matched for age, sex, income, and region of residence with 84, 960 control participants. The meteorological factors of mean, highest, and lowest temperatures; relative humidity; ambient atmospheric pressure; and air pollutant concentrations (SO2, NO2, O3, CO, and PM10 ) were analyzed to determine their associations with stroke. The odds ratios for stroke after exposure to each meteorological factor and air pollutant at 7 and 30 days were calculated in the stroke and control groups. Subgroup analyses were conducted according to age, sex, income, and region of residence. Results: The odds ratio associated with seven days of exposure to CO was 1.16 (95% CI = 1.04–1.31) in stroke patients. For 30 days of exposure, the odds ratio associated with CO was 1.16 (95% CI = 1.02–1.32) in stroke patients. Seven and 30 days of NO2 exposure were inversely associated with stroke. The odds ratio associated with seven days of exposure to O3 was 1.16 (95% CI = 1.01–1.32) in ischemic stroke patients. Both ischemic and hemorrhagic stroke had negative associations with 7 and 30 days of NO2 exposure. Conclusion: Both short- and long-term exposure to CO were related to stroke.